2010
DOI: 10.1590/s1516-44462010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of substance use during adolescent pregnancy in São Paulo, Brazil

Abstract: Objective: To investigate the association of cocaine and marijuana use during adolescent pregnancy in São Paulo-SP, Brazil, with psychiatric disorders, social status and sexual history. Method: One thousand pregnant adolescents were assessed by using the Composite International Diagnostic Interview, and sociodemographic and socio-economic questionnaire at the obstetric center of a public hospital in São Paulo. Hair samples were collected for analysis. Results: The following data were associated with cocaine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
2
0
5
Order By: Relevance
“…Some studies show that one in every three women consumes alcohol [21,25,26]. It is noteworthy that an association exists between mental health disorders and substance use [27,28]. Our results also showed a greater frequency of mental health disorders, compared with the pilot study, which could also have influenced such findings.…”
Section: Discussionsupporting
confidence: 46%
“…Some studies show that one in every three women consumes alcohol [21,25,26]. It is noteworthy that an association exists between mental health disorders and substance use [27,28]. Our results also showed a greater frequency of mental health disorders, compared with the pilot study, which could also have influenced such findings.…”
Section: Discussionsupporting
confidence: 46%
“…A recent study conducted in São Paulo, Brazil with teenage pregnant women concluded that there are mainly two risk factors related to the use of drugs during pregnancy: age under 14 years and 3 or more life sexual partners. Socioeconomic factors were not associated with higher risk of drug consumption during pregnancy (BESSA et al, 2010).…”
mentioning
confidence: 80%
“…La religión -ya sea la afiliación o la práctica habitual-es otro factor frecuentemente mencionado -en ocasiones como factor protector, en otras como elemento que propicia un mayor consumo de sustancias entre seguidores de algunas creencias-. Se encontraron, además, diferencias en raza, origen étnico y situación migratoria (ver Tabla 3; Ali, Davis, Simmons, & Ramroop, 2014;Assanangkornchai, Saingam, Apakupakul, & Edwards, 2016;Bessa et al, 2010;Bottorff et al, 2014;Davie-Gray, Moor, Spencer, & Woodward, 2013;De Santis et al, 2011;Lamy & Thibaut, 2010;Muckle et al, 2011;Onah, Field, van Heyningen, & Honikman, 2016;Peña & Matute, 2010;van Gelder et al, 2010;Wickersham et al, 2016).…”
Section: Consumo De Diversas Sustanciasunclassified
“…institucional a esta problemática (Assanangkornchai et al, 2016;Bessa et al, 2010;Bjønness, 2015;Bottorff et al, 2014;Davie-Gray et al, 2013;De Santis et al, 2011).…”
Section: Factores Vinculados Al Consumo De Drogas En El Embarazounclassified
See 1 more Smart Citation